The Analysis of the existence of Phi Fa of That Ing Hang Villagers NakhonKaiSonPhromWihanSavannakhet Province, Lao PDR - Thongmixay, Phra Vilaythong; Bhavanabodhikun, Phrakhru; Wongpornpavan, Chakkapan; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2025)
This research entitled “The Existence of Phi Fa According to the Beliefs of That Ing Hang Villagers, Kaysone Phomvihane City, Savannakhet Province, Lao People's Democratic Republic” aimed to: 1) study the historical background of Phi Fa, 2) investigate the beliefs concerning Phi Fa among the villagers of That Ing Hang, and 3) examine the existence of Phi Fa from the perspective of local beliefs. This qualitative research employed documentary study and fieldwork. Key informants consisted of 24 participants, including ritual practitioners, individuals who received healing through Phi Fa rituals, and community observers. Data were collected through in-depth interviews, participant observation, and focus group discussions. The data were analyzed using descriptive and inductive approaches. The findings revealed that: 1) Phi Fa is a traditional belief inherited from ancestors among Lao and Northeastern Thai communities, closely associated with the belief in Phaya Thaen, spirits, and supernatural powers believed to protect people and cure illnesses 2) the belief in Phi Fa among That Ing Hang villagers represents a folk belief system integrating animism and Buddhist teachings, significantly influencing local traditions, rituals, and ways of life 3) the existence of Phi Fa can be understood through cultural, anthropological, and folkloric perspectives. Although it cannot be scientifically verified, Phi Fa continues to function as a spiritual symbol that fosters faith, social cohesion, and cultural identity within the community